Artificial intelligence in dentistry—A review - Ding, Hao; Wu, Jiamin; Zhao, Wuyuan; Matinlinna, Jukka P.; Burrow, Michael F.; Tsoi, James K. H. (Frontiers in Dental Medicine, 2023)
Artificial Intelligence (AI) is the ability of machines to perform tasks that normally require human intelligence. AI is not a new term, the concept of AI can be dated back to 1950. However, it has not become a practical tool until two decades ago. Owing to the rapid development of three cornerstones of current AI technology – big data (coming through digital devices), computational power, and AI algorithm – in the past two decades, AI applications have been started to provide convenience to people’s lives. In dentistry, AI has been adopted in all dental disciplines, i.e. operative dentistry, periodontics, orthodontics, oral and maxillofacial surgery, and prosthodontics. The majority of the AI applications in dentistry go to the diagnosis based on radiographic or optical images, while other tasks are not as applicable as image-based tasks mainly due to the constraints of data availability, data uniformity, and computational power for handling 3D data. Evidence-based dentistry (EBD) is regarded as the gold standard for the decision-making of dental professionals, while AI machine learning (ML) models learn from human expertise. ML can be seen as another valuable tool to assist dental professionals in multiple stages of clinical cases. This review narrated the history and classification of AI, summarised AI applications in dentistry, discussed the relationship between EBD and ML, and aimed to help dental professionals to understand AI as a tool better to assist their routine work with improved efficiency.